APLIKASI MONITORING KEAMANAN JARINGAN DENGAN MENGGUNAKAN IDS DAN ROUTER MIKROTIK - Pidie Wiyanto; Amir Hamzah; Mohammad Sholeh (Jurnal Jarkom, 2015)
This study is aimed at making security application of computer network by using snort detection system method and mikrotik. Combining IDS method and IPTables mikrotik is to avoid intruder furthrmore, using web to make admin easily to monitor .This application aims to make system of network computer security easier, based on web and to be analyzed as well as controlled by administrator . this application is made to block ip address that is suspected bringing. The system is capable to processing output data from mikrotik, and it can also recognize all activities an intruder in attempt to infiltrate into the system by using port scanner, the ssh, ftp,then do the bloking of ip address that are considered as intruder after that the system will provide a report to the administrator through webserver of the presence of an intruder who trying to get into the system.